A case of massive pancreatic fluid collection managed with percutaneous pigtail drainage as step-up approach - Riyaz, Mohammad; Devakumar, Satish; Kamal, Harshit; Jeswanth, S. (International Surgery Journal, 2022)
A 19-year-old male presented to us with complain of acute epigastric pain for 2 weeks duration. The pain was dull aching in nature, radiating to back. On examination he was of average built and nutrition, dysnoic and tachypnoic with pulse rate of 140 /min, respiratory rate 26 /min, blood pressure 140/80 mmHg, saturation on room air 90%, bilateral (b/l) pedal edema present. On per abdomen examination abdomen was distended, fullness was present in bilateral upper abdomen. So, after thorough investigation, diagnosis of acute necrotizing pancreatitis was made and subsequently planned for ultrasonography (USG) guided percutaneous pigtail drainage as step-up approach in view of multiple loculated collections. Nasojejunal tube was inserted for entral nutrition. First perihepatic collection was drained on day 1, then lesser sac and pelvis drainage was done on day 2. At times, the collections may extend into the subhepatic space from the lesser sac through foramen of Winslow. Such subhepatic collections are intraperitoneal rather than retroperitoneal and there is a significant risk of peritoneal leak during endoscopic transmural drainage that may cause peritonitis. The collections may extend to either or both paracolic gutters retroperitoneally and at times to pelvis. In these retroperitoneal collections where endoscopic transmural drainage that may cause peritonitis, percutaneous pigtail drainage as a step-up approach is a feasible option.